PENGARUH PENAMBAHAN CACING SUTRA (Tubifex) SEBAGAI KOMBINASI PAKAN BUATAN TERHADAP EFISIENSI PEMANFAATAN PAKAN DAN PERTUMBUHAN LARVA IKAN LELE SANGKURIANG (Clarias gariepinus) - Atta Mullah; Nanda Diniarti; Baiq Hilda Astriana (Jurnal Perikanan Unram, 2019)
Catfish (Clarias sp.) Is one of the commodities featured fresh water to be cultivated and popular among the people. This dikarnakan owned catfish nutrition high in protein and bone-fortifying substances (calcium) is good for food. Catfish (Clarias sp.) included in the class of carnivorous fish and also includes scavengers, at the larval stages of catfish in desperate need of natural food such as sludge worms (Tubifex), which has a high protein value, The research was conducted for 30 days from the date July 31, 2019 until the date August 29, 2019, where research is conducted in the village of Langko, District Lingsar, West Lombok regency,This research was conducted with an experimental method using a completely randomized design (CRD) with four treatments and three replications that treatment A: Pellet 100% (control), B: Pellets 25% and sludge worms 75%, C: Pellet 50% and sludge worms 50 % and D: Pellets 75% and 25% sludge worms. The results showed that larval fish catfish (Clarias gariepinus) the survival rate (SR) was obtained in treatment B the highest, reaching 94.7% and the value of the lowest survival in treatment A is equal to 80%. ANOVA results showed no significant difference from the effect of the addition of sludge worms (Tubifex) as a combination of artificial feed for the maintenance of of the weight growth absolute length growth the absolute level of lifespan life, the efficiency of feed utilization and the emptying time hull.